(untitled) (Research Journal, 2025)
Today’s globalized economy; workers are increasingly looking for job opportunities beyond their home country in search of decent work and better livelihoods. In Nepalese context, foreign labor migration is also being more important for employment mainly among unemployed people and youths who entered in labor force market. It has brought impacts on different aspects of life including education. So, this study examines the foreign labor migration and its educational impact on enrollment of students in the study area. The study followed the qualitative method of study. The study revealed that foreign employment significantly impacts the declining enrollment of students in higher education, as many opt for immediate economic opportunities abroad. Interviews highlighted that financial constraints, societal influence, and limited career prospects in Nepal are key factors driving this trend. To mitigate the decline in higher education enrollment, it is essential to create better educational and career opportunities within the country. Strengthening support systems and raising awareness about the value of higher education can help retain students in domestic institutions.